Effect of Steel Fibers on the Mechanical Strength of Concrete - Muhamet Ahmeti; Driton Kryeziu; Mentor Ramadani (Salehan Institute of Higher Education, 2022)
The study is based on designing the mix design of the concrete for the class named MR_DK_E1: C30/37, one of the most widely used classes of normal concrete. To see the effect of the fibers on concrete, we will design three mixtures that in other components are similar to the first mixture